The New DSM-5 Impairment Criterion: A Challenge to Early Autism Spectrum Disorder Diagnosis? - Zander, E.; Bölte, Sven (Springer New York LLC, 2015)
The possible effect of the DSM-5 impairment criterion on diagnosing autism spectrum disorder (ASD) in young children was examined in 127 children aged 20–47 months with a DSM-IV-TR clinical consensus diagnosis of ASD. The composite score of the Vineland Adaptive Behavior Scales (VABS) served as a proxy for the DSM-5 impairment criterion. When applying a mild level of impairment (cutoff: 1 SD below the mean on the VABS), 88 % of the cases fulfilled the impairment criterion. Sixty-nine percent fulfilled the impairment criterion at a moderate level (1.5 SDs) and 33 % at a severe level (2 SDs). Findings indicate that a strict application of the new DSM-5 impairment criterion might compromise early diagnosis of ASD.